Comparative Analysis of Haemodynamic and Capnographic Changes in Laparoscopic Cholecystectomy and Open Cholecystectomy: A Randomised Clinical Study - Kaveri Das; Sudipa Paul; Pritanu Deb Baruah; Gunabhi Ram Das; Avishek Dutta Choudhury (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Laparoscopic cholecystectomy is now preferred over the open procedure due to advantages such as reduced blood loss and shorter hospital stays. However, concerns have been raised regarding the potential for increased Intra-abdominal Pressure (IAP) during laparoscopic procedures, which may impact haemodynamic stability and respiratory parameters. However, there is a lack of comprehensive analysis directly comparing both surgical approaches from both haemodynamic and capnographic perspectives. Aim: To compare the haemodynamic and capnographic changes between laparoscopic and open cholecystectomy. Materials and Methods: This randomised clinical study was conducted at Department of Anaesthesiology, Assam Medical College and Hospital, Dibrugarh, Assam, India from May 2021 to June 2022. The study included 300 patients scheduled for cholecystectomy, divided into two groups: Laparoscopic Cholecystectomy (LC) Group I (n=150) and Open Cholecystectomy (OC) Group II (n=150). Haemodynamic parameters, including Pulse Rate (PR), Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), Mean Arterial Pressure (MAP), and Oxygen Saturation (SpO2 ), were recorded. Capnographic parameters, such as End-Tidal Carbon Dioxide (EtCO2 ) levels, were also measured at regular intervals. Data analysis was performed using the student’s t-test and Chi-square test with Statistical Package for Social Sciences (SPSS) version 21.0 software and Microsoft excel. Results: There were no significant differences in age, body weight, and sex distribution between Group I and Group II. However, significant differences were observed in PR and SBP at 15 minutes (PR: 101.46 and 95.86; SBP: 148.57 and 140.97), 30 minutes (PR: 104.52 and 99.82; SBP: 141.28 and 136.07), and 45 minutes (PR: 102.52 and 97.70; SBP: 140.59 and 133.95) (p-value <0.01). Highly significant differences were observed in MAP and EtCO2 postinsufflation at 15 minutes (MAP: 118.38 and 108.61; EtCO2: 36.48 and 33.89), 30 minutes (MAP: 111.11 and 106.01; EtCO2: 41.02 and 36.15), 45 minutes (MAP: 110.73 and 103.48; EtCO2: 42.65 and 38.36), and 60 minutes (MAP: 106.08 and 101.45; EtCO2: 41.10 and 38.21) (p-value <0.01). DBP showed high significance at 15 minutes (103.21 and 93.23), 30 minutes (96.74 and 92.57), and 60 minutes (93.14 and 86.92) (p-value <0.01), and significant (p-value=0.01) at 45 minutes (95.53 and 87.59). Oxygen saturation showed significance (p-value <0.05) at 15 minutes (99.93 and 100). Conclusion: The present study demonstrated a significant increase in both haemodynamic and capnographic parameters, even in American Society of Anaesthesiologists (ASA) Grade-I and Grade-II patients undergoing laparoscopic cholecystectomy compared to the open surgical technique. These findings emphasise the need for careful monitoring during laparoscopic procedures.